MiR-1-3p Suppresses Colorectal Cancer Cell Proliferation and Metastasis by Inhibiting YWHAZ-Mediated Epithelial–Mesenchymal Transition - Du, Guanghong; Yu, Xuelian; Chen, Yun; Cai, Wangting (Frontiers in Oncology, 2021)
Background: Colorectal cancer (CRC) is regarded as one of the most common malignancies in the world. MiR-1-3p was reported to be a tumor suppressor in CRC. However, the mechanisms have not been fully elucidated. Methods: To identify CRC-associated miRNA, microarray dataset GSE30454 was downloaded from the Gene Expression Omnibus database (GEO) and miR-1-3p was screened out as a candidate. The expression of miR-1-3p was detected using quantitative real-time polymerase chain reaction (qRT-PCR) in CRC cell lines and tissues. CCK-8 assay and transwell invasion assay were performed to determine CRC cell lines proliferation and invasion, respectively. The levels of YWHAZ and EMT-associated proteins were detected using western blotting. Results: Bioinformatic analysis showed that miR-1-3p was downregulated in CRC tissues, which is verified by our experimental validation. The overexpression of miR-1-3p significantly suppressed CRC cells proliferation and invasion. Further studies showed that YWHAZ was a direct target of miR-1-3p and mediated epithelial–mesenchymal transition (EMT) modulated by miR-1-3p. Conclusion: Our results demonstrated that miR-1-3p suppresses colorectal cancer cell proliferation and metastasis through regulating YWHAZ-mediated EMT, which may support a novel therapeutic strategy for CRC patients.